KARAKTERISTIK MUTU PATI UBI TALAS (Colocasia esculenta) PADA PERBANDINGAN AIR DENGAN HANCURAN UBI TALAS DANKONSENTRASI NATRIUM METABISULFIT - Saputra, Farhandi; Hartiati, Amna; Admadi H, Bambang (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 4 No 1 (2016): Maret, 2016)
This research were aimed to 1) find out the effect of comparison between water and taro and sodium metabisulphite consentration as marinade solution on the quality of taro starch, 2) to find out the best characteristic of taro starch based on comparison of water and taro and sodium metabisulphite consentration as marinade solution. This study used a factorial Randomized Block Design with factorial pattern. The first factor was the comparison of water and taro consists of 3 levels namely 2:1, 3:1 and 4:1 and the second factor wasconcentration of sodium metabisulphite consetration consists of 3 levels namely 0 %, 0.2% and 0.3%. Each treatment grouped into two based on the time implementation. Variables observed were water content, starch content, amilosa, organoleptic test and yield. The best treatment was determined with effectiveness index. The results showed that the comparison of water and taro and sodium metabisulphite consentration as marinade solution had high significantly effect on water content and amilosa content at characteristic of taro starch, while its interaction was not significant. Comparison of water and sodium metabisulphite substance and its interaction had significantly effect on starch content of taro and its yield. The treatment concentration of sodium metabisulphite 0.3 % and comparison water and taro 4:1obtained the best quality of taro starch with 8.87 % water content, 65.23 % starch content, 15.75 % amilosa content, 3.84 multiple comparison test (near to Refrence) and 21.58 % yield. Keywords : comparison of water, sodium metabisulphite, starch, taro
Keywords: 89